Plant Alkaloids as Antiplatelet Agent: Drugs of the Future in the Light of Recent Developments - Ain, Qurrat-Ul-; Khan, Haroon; Mubarak, Mohammad S.; Pervaiz, Aini (Frontiers in Pharmacology, 2016)
The alkaloid is a class of naturally occurring organic nitrogen-containing compounds that are frequently found in the plant kingdom. Many alkaloids are valuable medicinal agents that can be utilized to treat various diseases including malaria, diabetics, cancer, cardiac dysfunction etc. Similarly, platelet aggregation beyond the purpose of homeostasis is the underlying cause of blood clotting related diseases. This review presents a thorough understanding of alkaloids as antiplatelet agents with a possible mechanism of action based on the literature of the last decade. In addition, this review will address the antiplatelet activity of alkaloids and their medicinal usage as potent antiplatelet agents with a description of structural relationship activity and possible lead compounds for future drug discovery.